Analisis Pengaruh Leverage dan Profitabilitas Terhadap Nilai Perubahaan Pada Bank Digital Yang Tercatat di Bursa Efek Indonesia - Erisabet, Feni; Habiburahman (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the effect of Leverage and Profitability on Company Value in digital banks listed on the Indonesia Stock Exchange during the period 2021-2023 The purpose of this study is to provide a deeper understanding of how certain financial factors, such as Leverage and Profitability, affect the valuation of companies in the rapidly growing digital banking sector in the digitalization era. with a data panel approach to analyze the relationships between variables. The sampling technique used was purposive sampling, where five digital bank companies were selected based on certain criteria, such as completeness of financial statements and operational consistency during the research period. The data used in this study is in the form of annual financial statements published by each digital bank, with Leverage variables measured using Debt to Equity Ratio (DER) and Profitability measured using Return on Assets (ROA). Data analysis was carried out using multiple linear regression to test the simultaneous and partial influence between independent variables (Leverage and Profitability) on dependent variables (Company Value). The results show that simultaneously, Leverage and Profitability have a significant influence on Company Value Partially, Leverage has a negative influence on Company Value, while Profitability has a positive influence. Hasıl ını emphasized that increased Profitability can drive the growth of Company Value, while high Leverage can actually be a inhibiting factor This research contributes to providing insight to financial managers and stakeholders on the importance of balancing Profitability and Leverage management to maintain and increase the value of companies in the Indonesian capital market.